2014
DOI: 10.1177/1557988314559241
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Shag Dirty Girls”

Abstract: Understanding and addressing the sexual risk taking of young men remains a key research, policy, and practice concern in attempts to improve the emotional and physical sexual health of young men and their sexual partners. This article explores one of the ways in which young men attempt to mitigate sexual risk through the assigning of labels to particular young women and using these as a basis for their decisions in relation to sexual activity, contraception, and condom use. The article uses the lens of hegemon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Explanations for low levels of STI risk perception among those at risk have included lack of knowledge about STIs and their prevalence [15] , [31] , lack of symptoms [32] , and optimistic bias [32] , [33] . It has also been shown that people misjudge their sexual partners' risk [34] , and studies in several populations have described the use of inappropriate markers of partners' STI risk in deciding whether or not to use a condom, including partners' reputation, where they live, demeanour, physical attributes including clothing and personal hygiene, and lack of any visible STI symptoms [15] , [31] , [33] , [35] . Evidence that people generally overestimate the risk of ‘visible’ phenomena and underestimate the risk of less visible phenomena (‘availability bias’) [36] suggests that the often invisible and stigmatised nature of STIs may contribute to underestimation of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations for low levels of STI risk perception among those at risk have included lack of knowledge about STIs and their prevalence [15] , [31] , lack of symptoms [32] , and optimistic bias [32] , [33] . It has also been shown that people misjudge their sexual partners' risk [34] , and studies in several populations have described the use of inappropriate markers of partners' STI risk in deciding whether or not to use a condom, including partners' reputation, where they live, demeanour, physical attributes including clothing and personal hygiene, and lack of any visible STI symptoms [15] , [31] , [33] , [35] . Evidence that people generally overestimate the risk of ‘visible’ phenomena and underestimate the risk of less visible phenomena (‘availability bias’) [36] suggests that the often invisible and stigmatised nature of STIs may contribute to underestimation of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Once boys reach adolescence, pressure to engage in heterosexual interactions becomes a salient component of normative masculine behaviour (Reigeluth and Addis 2016). Norms dictate that men maintain a heterosexual self-presentation, engage with multiple romantic partners, and assert their right to have power over women to be traditionally masculine, and failing to meet standards can undermine their sense of masculinity (Closson et al 2019;Limmer 2016). Concern with displaying sexual voracity and skill (related to Heterosexual Self-Presentation norms) can lead to avoidance of contraceptives such as condoms (Limmer 2016), and endorsement of Power Over Women in marriage specifically predicted men's rejection of vasectomies (Hernández-Aguilera and Marván 2016).…”
Section: Masculinity and Health Decision-makingmentioning
confidence: 99%
“…Norms dictate that men maintain a heterosexual self-presentation, engage with multiple romantic partners, and assert their right to have power over women to be traditionally masculine, and failing to meet standards can undermine their sense of masculinity (Closson et al 2019;Limmer 2016). Concern with displaying sexual voracity and skill (related to Heterosexual Self-Presentation norms) can lead to avoidance of contraceptives such as condoms (Limmer 2016), and endorsement of Power Over Women in marriage specifically predicted men's rejection of vasectomies (Hernández-Aguilera and Marván 2016). Other masculine norms such as Self-Reliance and Emotional Control likely block men from seeking medical assistance in relation to their reproductive health (Yousaf, Grunfeld, and Hunter 2015).…”
Section: Masculinity and Health Decision-makingmentioning
confidence: 99%
“…Once boys reach adolescence, pressure to engage in heterosexual interactions becomes a salient component of normative masculine behaviour (Reigeluth and Addis 2016). Norms dictate that men maintain a heterosexual self-presentation, engage with multiple romantic partners, and assert their right to have power over women to be traditionally masculine, and failing to meet standards can undermine their sense of masculinity (Closson et al 2019;Limmer 2016). Concern with displaying sexual voracity and skill (related to Heterosexual Self-Presentation norms) can lead to avoidance of contraceptives such as condoms (Limmer 2016), and endorsement of Power Over Women in marriage specifically predicted men's rejection of vasectomies (Hernández-Aguilera and Marván 2016).…”
Section: Masculinity and Health Decision-makingmentioning
confidence: 99%
“…Norms dictate that men maintain a heterosexual self-presentation, engage with multiple romantic partners, and assert their right to have power over women to be traditionally masculine, and failing to meet standards can undermine their sense of masculinity (Closson et al 2019;Limmer 2016). Concern with displaying sexual voracity and skill (related to Heterosexual Self-Presentation norms) can lead to avoidance of contraceptives such as condoms (Limmer 2016), and endorsement of Power Over Women in marriage specifically predicted men's rejection of vasectomies (Hernández-Aguilera and Marván 2016). Other masculine norms such as Self-Reliance and Emotional Control likely block men from seeking medical assistance in relation to their reproductive health (Yousaf, Grunfeld, and Hunter 2015).…”
Section: Masculinity and Health Decision-makingmentioning
confidence: 99%